Kinerja Karyawan Melalui Kompetensi dan Motivasi - Mansyur, Syahrul; Maedina, Rosida (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2024)
The purpose of this study is to examine the effect of work competence and motivation on employee performance at PT. Midi Utama Indonesia Tbk Makassar. This type of research is quantitative. The population constitutes the overall subject of the study. The population of this study is all employees of PT Midi Utama Indonesia Tbk Makassar. The sample is part of the number and characteristics possessed by that population. The number of samples in this study using the slovin formula was 70 respondents who were employees of PT. Midi Utama Indonesia Tbk Makassar. The data analysis method uses multiple linear regression analysis (Multiple Regression). The results found that competence has a significant effect on employee performance; Work motivation was found to have a significant effect on employee performance.